Infant mortality due to avoidable causes of children 0-4 years old in Maranhão between 2015 to 2019 (Research, Society and Development, 2022)
Objective: to describe the evolution of infant mortality from 0 to 4 years old by preventable causes in the state of Maranhão, Brazil, in the period 2015-2019. Method: This is a descriptive ecological study with a quantitative approach. The study will be developed from secondary data available in the SUS Informatics System (DATASUS) notified by the state of Maranhão between 2015 and 2019. Results: an increase in death rates was observed in three groups: reduceable by attention to women in pregnancy, adequate attention to the newborn and by actions of diagnosis and adequate treatment. In relation to the rates of deaths from preventable causes that can be reduced by adequate care for women during childbirth and promotion actions linked to care actions, there was a reduction in the rates, which in the year 2017 showed 0.213 and 0.173 respectively; similarly to the rates, the proportion of deaths also had its most evident increase from the year 2017. In it, deaths due to gestational causes present 31.9% of proportion, the causes related to the NB, 25.8% and those related to care actions 13.3%. The only cause that shows a steady decrease from 2017 was birth-related, obtaining 16.4% in 2018 and 14% in 2019. Conclusion: the reduction in infant mortality from preventable causes is below expectations in the state of Maranhão, especially in reference to preventable causes related to adequate care for women during pregnancy, adequate care for women in childbirth and adequate care for the newborn and resulting from actions of diagnosis and adequate treatment.